Prinsip Kehati-Hatian Bagi Bank Umum Dalam Penyerahan Perkerjaan Kepada Perusahaan Lain - Sandra Dewi, Aliya; Suwarni Herry, Ayni (Universitas Muhammadiyah Bima, 2022)
In contracting work, there are three groups of people who are interested, namely the company that provides chartering work (the company that provides the charter), the company that accepts the work of chartering (the company that accepts the charter), and workers. The Contracting Company may submit part of the work implementation to the Contracting Recipient Company. This is carried out through a written Contract of Work Agreement. It must contain provisions that guarantee the fulfillment of the rights of workers/laborers in the emerging employment relationship. Since December 9, 2011 Bank Indonesia issued Bank Indonesia Regulation No.13/25/PBI/2011 concerning Prudential Principles for Commercial Banks in Delegating Work to Other Companies, requiring banking companies in Indonesia to follow these rules in drafting Job Contracting Agreements with Another company. This is inseparable from the decision of the Constitutional Court no. 27/PUU-IX/2011 decision dated January 17, 2012. Based on the description above, the author feels interested in researching this problem and intends to put the results of the research into a scientific paper entitled The Effect of Bank Indonesia Regulation No. 13/25/PBI/2011 concerning Prudential Principles for Commercial Banks in Delegating Work to Other Companies with the Decision of the Constitutional Court No. 27/PUU-IX/2011 Related to the Implementation of Part of the Work between Banking Companies and Non-Banking Companies.